The Effect of Using Kale Vegetable Extracts, Kailan Vegetables, and Mustard Greens Vegetables in Bakpao Making on The Physical and Sensory Quality - Wahyudi, Savina Putri; Cahyana, Cucu; Kandriasari, Annis (Advances In Social Humanities Research, 2024)
The research aimed to analyze the effect of using kale, kailan and mustard green vegetable extracts in making bakpao on physical and sensory quality. This research was conducted at the Bread and Patisserie Processing Laboratory, Culinary Education Study Program, Faculty of Engineering, Jakarta State University. The method used in this research is an experimental method which begins with a physical test by measuring the volume of the bakpao and the height of the bakpao, which is followed by a sensory test on 45 trained panelists, namely students of the Culinary Education Study Program who have passed the advanced bread processing course. The results of the research show that the results of hypothesis testing using the Kruskal Wallis test with a significance level of ? (0.05) show that there is no effect of using extracts of kale, kailan vegetables and green mustard greens in making bakpao on sensory quality in all aspects. The results of physical measurements of volume and height with the greatest values ??were obtained by kailan vegetable extract with a volume of 103.33 cm3 and an average height of 3.97 cm. The conclusion of the results of this research is based on the results of physical tests that the bakpao using kailan vegetables have advantages in terms of volume and height, so they are the recommended formula.